Важливість та інструментарій маркетингових досліджень при виході вітчизняних підприємств на міжнародні ринки - Ванькович, Л. Я.; Паук, Н. І.; Vankovych, L. Ya.; Pauk, N. I. (Видавництво Львівської політехніки, 2023)
У статті визначено сутність терміна “маркетингові дослідження”, описано процес маркетингових досліджень та наведено перелік основних видів досліджень. Автори узагальнили можливі способи використання інформаційних технологій для ведення маркетингових досліджень, зосередивши увагу на можливих впливах маркетингових досліджень на успішність виходу компаній на міжнародний ринок. На основі аналізування успішних історій використання маркетингових досліджень зроблено висновок про ефективність таких досліджень та наведено приклади результатів.

The article presents the concept of marketing research, its methodology and a brief overview of key categories of research. The authors define marketing research as the collection, processing, analysis and synthesis of data to support marketing decisions and the activities of enterprises in the market by reducing uncertainty and risk. Four types of basic marketing research are described, including primary research, secondary research, quantitative research, and qualitative research. Each of the four categories of market research has its advantages and disadvantages. A company that conducts mixed-methods market research gets the best of both worlds by combining different methods. When done correctly, this can increase the accuracy and standardization of the results, giving your research and conclusions greater depth and breadth. This article discusses the potential applications of information technology in marketing research and how it can impact companies' global operations. A wide range of information technologies, such as social media analysis, eye-tracking technology, artificial intelligence, online surveys, and virtual reality, can be used by marketers to conduct research. Social media can offer useful data on demographics, sentiment analysis, and brand mentions. Eye-tracking technology can help marketers understand how consumers react to ads and products. A lot of consumer data can be studied using artificial intelligence. The authors have identified four main possible areas of influence of market research on companies' entry into international markets. These include finding target markets, creating effective marketing strategies, mitigating risks, and determining the potential size and expansion of global markets. The conclusions drawn from the review of examples of successful applications of market research have demonstrated the value of such research and allowed us to illustrate some of its results. Any business, including the logistics company Nova Poshta, must conduct market research to be successful. Using methods such as focus groups, focus interviews, and online technologies, they conducted an international market research on the organization and management of logistics. In general, market research can help companies maximize their efforts and resources to enter new markets, which can increase their profitability and market share.
The importance and toolkit of marketing research while launching domestic enterprises in international markets
Keywords: маркетингове дослідження; види досліджень; процес маркетингових досліджень; міжнародна діяльність; інформаційні технології в маркетингових дослідженнях; marketing research; types of research; marketing research process; international activity; information technology in marketing research; 330.341